0D to 3D Coordination Assemblies Engineered on Silver(I) Salts and 2‐(Alkylsulfanyl)azine Ligands: Crystal Structures, Dual Luminescence, and Cytotoxic Activity. Issue 17 (21st April 2020) - Rogovoy, Maxim I.; Frolova, Tatiana S.; Samsonenko, Denis G.; Berezin, Alexey S.; Bagryanskaya, Irina Yu.; Nedolya, Nina A.; Tarasova, Olga A.; Fedin, Vladimir P.; Artem'ev, Alexander V.
Abstract : The potential of 2‐(alkylsulfanyl)azine ligands for crystal engineering of functional Ag (I) complexes has been firstly demonstrated. The reaction of AgNO3, AgClO4 and AgOTf with 2‐(alkylsulfanyl)pyridines, ‐pyrimidines, and ‐quinolines gives a series of new Ag (I) compounds that range from mono‐ and dinuclear complexes to chain (1D), layered (2D) and framework (3D) coordination polymers (CPs). 2‐(Alkylsulfanyl)pyridines and ‐pyrimidines, depending on the reaction conditions, are assembled either into molecular complexes or CPs, while 2‐(alkylsulfanyl)quinolines afford dinuclear complexes exclusively. The most of compounds engineered feature site‐specific interactions such as Ag··· Ag, Ag··· O, and Ag··· S ones. The 2‐(methylsulfanyl)quinoline (2‐MeSQn) complex, [Ag2 (2‐MeSQn)2 (NO3 )2 ], displays room temperature intraligand (IL) phosphorescence, while the 2‐(methylsulfanyl)pyridine‐derived CPs emit dual luminescence expressed by IL fluorescence and phosphorescence. Moreover, cytotoxic activity of the compounds synthesized has been evaluated against hTERT lung fibroblasts, HeLa, MCF7, HepG2 and A549 cancer cells. Abstract : A series of molecular complexes as well as 1D, 2D, and 3D coordination polymers has been assembled reacting Ag I salts with 2‐(alkylsulfanyl)pyridines, ‐pyrimidines, and ‐quinolines. The photoluminescence and cytotoxicity of these compounds are discussed.